PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. TIKI JNE CABANG S. PARMAN JAKARTA BARAT - Witari; Hanis, Umar (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work stress variables and the work environment on the performance of employees of PT TIKI JNE S.Parman Branch, West Jakarta. This type of research uses associative quantitative. The data analysis methods used in this research are validity test, reliability test, classical assumption test, descriptive analysis, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient of determination test, t test and f test. The number of samples in this research was 60 respondents. The sampling technique used saturated sampling and a sample of 60 PT employees was obtained, TIKI JNE S. Parman Branch, West Jakarta. The analysis in this research uses simple and multiple linear regression analysis. Relationships were analyzed using multiple linear regression. With the multiple linear regression equation, namely Y = 36.752 - 0.613 X1 + 0.223 X2. The results of this research show that work stress has a negative effect on employee performance with a calculated t value of – 8.695 > t table 2.002, so the hypothesis is accepted. Work environment variables have a positive influence on employee performance with a calculated t value of 4.654 > t table 2.002 so the hypothesis is accepted. Work stress and the work environment simultaneously and significantly influence employee performance with a calculated f value of 48.728 > f table 2.77. The coefficient of determination value shows that work stress and the work environment contribute to employee performance by 63.1%, while the remaining 36.9% is influenced by other factors not studied.